Regulation of human Th9 cell differentiation by lipid modulators targeting PPAR-γ and acetyl-CoA-carboxylase 1 - Peesari, Swetha; McAleer, Jeremy P. (Frontiers in Immunology, 2024)
CD4 T cell activation induces dramatic changes to cellular metabolism for supporting their growth and differentiation into effector subsets. While the cytokines IL-4, TGF-β and IL-21 promote differentiation into Th9 cells, metabolic factors regulating this process remain poorly understood. To assess the role of lipid metabolism in human Th9 cell differentiation, naïve CD4 T cells were purified from blood of healthy volunteers and cultured in the presence or absence of compounds targeting PPAR-γ, acetyl-CoA-carboxylase 1 (ACC1), and AMP-activated protein kinase (AMPK) for four days. Th9 cell differentiation significantly increased PPARG expression, and the PPAR-γ agonist rosiglitazone suppressed IL-9 in a dose-dependent manner. The rosiglitazone-mediated suppression also occurred in the presence of the glucose metabolism inhibitor 2-deoxy-D-glucose, suggesting it was independent of glycolysis. On the other hand, the PPAR-γ antagonist GW9662 had no significant effect on IL-9 production. Next, the role of fatty acid synthesis was tested by treating cells with inhibitors of ACC1 (TOFA) or AMP-activated protein kinase (AMPK; dorsomorphin). We demonstrate reciprocal functions for these enzymes, as ACC1 inhibition substantially increased IL-9 production, whereas AMPK inhibition resulted in undetectable levels. TOFA also decreased expression of ACACA, the gene encoding ACC1, demonstrating regulation at the transcriptional level. Finally, combining TOFA treatment with exogenous oleic acid restored IL-9 back to the levels in control Th9 cultures, suggesting that ACC1 suppresses Th9 differentiation through fatty acid synthesis. Overall, our data demonstrate that lipid regulators associated with intracellular fatty acid accumulation suppress Th9 cell differentiation. These findings may have clinical implications for conditions associated with elevated IL-9 production.